Description of a new species of Pareiorhina (Siluriformes: Neoplecostominae) from Rio São Francisco basin - Roxo, Fábio Fernandes; de Souza Da Costa E Silva, Gabriel; Mehanna, Mahmoud; Oliveira, Claudio (Zootaxa, 2012)
A new species of Pareiorhina (Neoplecostominae) from the Rio São Francisco basin, Minas Gerais State, Brazil, is de-scribed. The new species is distinguished from its congeners (Pareiorhina brachyrhyncha, P. carrancas, and P. rudolphi)by traits related to small plates covered with odontodes randomly distributed on the abdomen, minute lateral cusps on theteeth, pointed odontodes covering pectoral, pelvic, and anal-fin first rays, caudal-fin being completely dark with one hy-aline bar, absence of a ridge on the postdorsal surface of trunk, shape of premaxillae and dentaries, and by the absence of odontodes at the ventral tip of the snout.